Linseed (Linum Usitatissimum L) Growth And Yield Influenced By Boron And Zinc Application In Central Plain Zone Of Uttar Pradesh (International Journal of Food and Nutritional Sciences, 2021)
A field experiment was conducted during the Rabi season of 2020-21 at the Agronomy Research Farm of Faculty of Agricultural Sciences and Allied Industries; Rama University, Kanpur Nagar, Uttar Pradesh. Three replications were used in the randomized block design experiment. The 9 treatments included basal application of ZnSO4 @ 20 kg/ha, foliar spray of Zn-EDTA @ 0.5% at 40 days after sowing, basal application of ZnSO4 @ 20 kg/ha + foliar spray Zn- EDTA of @ 0.5% at 40 days after sowing, basal application of borax @ 1.5 kg/ha, foliar spray of B- EDTA @ 0.3% at 40 days after sowing, basal application of borax @ 1.5 kg/ha + foliar spray of B-EDTA @ 0.3 at 40 days after sowing, basal application of ZnSO4 @ 20 kg/ha + borax @ 1.5 kg/ha, foliar spray of Zn-EDTA @ 0.5% + B-EDTA @ 0.3% at 40 days after sowing and control. Treatment Foliar spray of Zn-EDTA @ 0.5% + B-EDTA @ 0.3% at 40 days after sowing recorded significantly higher growth, yield attributes and seed yield. With a foliar spray of Zn-EDTA @ 0.5% + B-EDTA @ 0.3 % at 40 days after sowing and a basal application of ZnSO4 @ 20 kg/ha + borax @ 1.5 kg/ha, the maximum seed yield (2,047 kg/ha), gross monetary return (Rs.92,116/ ha) and net monetary return (Rs.65,990/ha) and benefit cost ratio (3.46:1) were recorded.